The Influence of Online Learning Media on Students' Learning Outcomes: Survey in SMA 1 Cawang Baru Jakarta - Nadiah; Tsania Nabilah (CV ODIS, 2023)
When online learning media is used effectually, it improves students’ learning outcomes. Conversely, the results may not be beneficial if you do not use inappropriate online learning media that do not satisfy students' needs. The purpose of this study is to collect valid data on the learning outcomes of survey students at SMA 1 Cawang Baru Jakarta using online learning media.